Experience of using plant complexes in physiological completion of lactation - N. V. Kosei; O.V. Zanko; L.А. Vasylchenko; N.V. Iarotska (Publishing House TRILIST, 2021)
Ending breastfeeding is often quite a challenge for women, justifying the need for qualified medical counseling and accompaniment by a doctor. Quite frequently during weaning the baby, women complain about pain, discomfort and swelling of the breasts, which affects their overall physical and psychological well-being. However, due to possible rather serious side effects, medical support for stopping lactation is mostly recommended for women with clinical indications. Research aim: to determine the effectiveness of the proposed method with Normomens for physiological completion of lactation. Materials and methods. The study involved 65 women with an average duration of lactation 9 ± 1.23 months. Patients were divided into two groups: group 1 included 34 women who received Normomens according to the scheme to stop lactation; group 2 included 31 patients who did not receive any medication. Patients were gynecological examined and counseled by oncologist. Patients' diaries included questions about the duration of lactation, presence and severity of mastalgia according to the Visual Analogue Scale, necessity of analgesics, frequency of breast pumping per day, features of psycho-emotional state according to the Hospital Anxiety and Depression Scale. Prolactin levels were also determined at the screening visit and on 25th day after weaning. Results. On the background of Normomens use the process of lactation completion was significantly easier, its completion came mostly on the 3-4 day after drug use, patients almost never complained of pain and discomfort in mammary glands, they less frequently breast pumped and had a more stable psycho-emotional state compared to the control group. Рrolactin level with usage of Normomens had a quick decrease compared to the control group. Conclusion. Normomens using for support the physiological finishing of lactation lead to acceleration of involutive processes in mammary glands, reduces pain severity and prevented psycho-emotional disorders in women.